Correction to: The Effect of Immediate Self-Myofascial Release and Static Stretching of the Gastrocnemius Muscle and Plantar Fascia in the Superficial Back Line on Range of Motion and chronic Neck Pain: A Randomized Clinical Trial - Marzieh Behnampour; Amir Hossein Barati; Behrouz Jafari; Mehrdad Bahramian (Journal of Mazandaran University of Medical Sciences)
Marzieh Behnampour1, Amir Hossein Barati2, Behrouz Jafari3, Mehrdad Bahramian4